2004
DOI: 10.1111/j.0962-1075.2004.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Plodia interpunctella lepidopteran cells and effects of 20‐hydroxyecdysone

Abstract: We have investigated the molecular and cellular mechanisms involved in the control of insect cell cycle by 20-hydroxyecdysone (20E) using the IAL-PID2 cell line established from imaginal wing discs of Plodia interpunctella. We first defined conditions for use of hydroxyurea, a reversible inhibitor of DNA synthesis, in order to synchronize the IAL-PID2 cells in their division cycle. A high degree of synchrony was reached when cells were exposed to two consecutive hydroxyurea treatments at 1 mm for 36 h spaced 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In higher organisms, steroid hormones control a variety of cellular functions, including cell proliferation, expansion, differentiation and programmed cell death (Hong et al, 2007;Vujovic et al, 2007;Li et al, 2007;Hsieh et al, 2007;Gao et al, 2006;Kilpatrick et al, 2005;Champlin and Truman, 1998;Siaussat et al, 2004aSiaussat et al, , b, 2007. In insects, the steroid hormone 20-hydroxyecdysone (20E), which belongs to the ecdysteroid family, is responsible for the radical reorganization of the body form that occurs at metamorphosis (Riddiford and Truman, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In higher organisms, steroid hormones control a variety of cellular functions, including cell proliferation, expansion, differentiation and programmed cell death (Hong et al, 2007;Vujovic et al, 2007;Li et al, 2007;Hsieh et al, 2007;Gao et al, 2006;Kilpatrick et al, 2005;Champlin and Truman, 1998;Siaussat et al, 2004aSiaussat et al, , b, 2007. In insects, the steroid hormone 20-hydroxyecdysone (20E), which belongs to the ecdysteroid family, is responsible for the radical reorganization of the body form that occurs at metamorphosis (Riddiford and Truman, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The IAL-PID2 cells respond to treatment with 20E by the arrest of cell growth and longterm spectacular morphological transformations (Couderc et al, 1987;Dinan et al, 1990;Siaussat et al, 2004a, b). Fluorescent flow cytometry analysis of the P. interpunctella IAL-PID2 cell-cycle have shown that 20E-induced proliferative arrest results from a blockage of cells in the G2/M phase (Siaussat et al, 2004a;Mottier et al, 2004;Stevens et al, 1980). The cell-cycle is regulated by the action of a family of serine/threonine kinases known as cdks.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of various insect and mammalian cell lines that have retained a sensitivity to steroid hormones has provided new possibilities for specifying the mode of action of these hormones in the control of cellular processes. MCF-7, MDA-MB-231 breast cancer cells from human, MBA-15 osteoblastic cells from mouse, Kc embryonic cells from D. melanogaster Diptera as well as IAL-PID2 epidermal cells from Plodia interpunctella Lepidoptera respond to steroid hormones treatment by the arrest of cell growth and long-term spectacular modifications in the shape of cells [24][25][26][27][28][29][30]. In Kc and MBA-15 cells, it has also been described that morphological transformations were accompanied by a redistribution in cytoplasmic microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…An Indian meal‐moth cell line, IAL‐PID2, has been established from pupally committed imaginal wing discs of Plodia interpunctella (Lynn & Oberlander, 1983). A 20E treatment evokes an inhibition of cell proliferation by the blocking of IAL‐PID2 cells in G2/M and a long‐term morphological differentiation (Cassier et al ., 1991; Porcheron et al ., 1991; Mottier et al ., 2004; Siaussat et al ., 2004b). The cloning of several cDNA sequences encoding Plodia B‐type cyclin (PcycB), ecdysone receptor B1‐isoform (PIEcR‐B1) and HR3 transcription factor (PHR3) has been reported (Debernard et al ., 2001; Mottier et al ., 2004; Siaussat et al ., 2004a).…”
Section: Introductionmentioning
confidence: 99%